2021
DOI: 10.31332/robust.v1i1.2620
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh NPF Dan FDR Terhadap ROA Bank Syariah Di Indonesia

Abstract: Penelitian ini dilakukan untuk menguji pengaruh Non Performing Financing (NPF) dan Financing to Deposit Ratio (FDR) terhadap Return On Asset (ROA) perbankan syariah di indonesia. Sampel yang digunakan dalam penelitian ini sebanyak 7 perusahaan perbankan syariah dengan rentang waktu pengamatan dari 2014 – 2018. Data dalam penelitian ini diolah menggunakan Eviews 10. Hasil penelitian menunjukkan bahwa NPF terhadap ROA memiliki nilai probabilitas atau signifikansi sebesar 0.0161 dan nilai Coefficient Beta sebesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 1 publication
4
3
0
8
Order By: Relevance
“…The existence of these five principles makes banks not worry about the flow of funds distributed to customers will be in arrears, so that FDR does not have an impact on financial performance (Kartika et al, 2020). This result is also in line with previous studies which found that FDR had no significant effect on financial performance (Rohansyah, 2021;Wibisono & Wahyuni, 2017).…”
Section: Effect Of Fdr On Roasupporting
confidence: 87%
See 2 more Smart Citations
“…The existence of these five principles makes banks not worry about the flow of funds distributed to customers will be in arrears, so that FDR does not have an impact on financial performance (Kartika et al, 2020). This result is also in line with previous studies which found that FDR had no significant effect on financial performance (Rohansyah, 2021;Wibisono & Wahyuni, 2017).…”
Section: Effect Of Fdr On Roasupporting
confidence: 87%
“…Several previous studies have proven that CAR (Syamni et al, 2018;Yusuf & Surjaatmadja, 2018), NPF (Dodi et al, 2018;Nahar & Prawoto, 2017), SIZE (Astutiningsih & Baskara, 2019;Yatiningsih & Chabachib, 2015) and FDR (Almunawwaroh & Marliana, 2018;Pravasanti, 2018;Pritadyana et al, 2019) are factors that have a significant effect on financial performance. However, other studies have found different things, where CAR (Muchtar et al, 2021;Wibisono & Wahyuni, 2017), NPF (Muchtar et al, 2021;Widyaningrum & Septiarini, 2015), SIZE (Vernanda & Widyarti, 2016;Yusuf, 2017) and FDR (Agusto, 2021;Rohansyah, 2021) have no significant effect on financial performance. This shows that there are inconsistencies and differences among researchers regarding the effect of CAR, NPF and SIZE on financial performance, thus encouraging the authors to review them again.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The movement of ups and downs of NPF affects the financial performance of Islamic banks. Financing risk measured using NPF is in line with research conducted by Rohansyah et al (2021), Welly and Hari (2018) and Pramono and Widiarto (2019) which shows that NPF has a significant negative effect on the financial performance of Islamic banks. Thus, the research hypothesis can be formed as follows:…”
Section: Effect Of Financing Risk On Financial Performancesupporting
confidence: 81%
“…Pendapat Mudrajad Kuncoro dan Suhardjono, bertambahnya porsi prosentase CAR menimbulkan ROA meniliki banyak keuntungan yang didapat dan sebaliknya. Selaras dengan itu, diperoleh kaitan CAR dan ROA berbanding lurus (Rohansyah, 2021).…”
Section: Pendahuluanunclassified